2019
DOI: 10.3389/fphy.2019.00082
|View full text |Cite
|
Sign up to set email alerts
|

Superconductive REBCO Thin Films and Their Nanocomposites: The Role of Rare-Earth Oxides in Promoting Sustainable Energy

Abstract: The lossless transmission of direct electrical currents in superconductors is very often regarded as an "energy superhighway" with greatly enhanced efficiency. With the discovery of high temperature superconductors (HTS) in the late eighties, the prospect of using these materials in efficient and advanced technological applications became very prominent. The elevated operating temperatures as compared to low temperature superconductors (LTS), relaxing cooling requirements, and the gradual development of facile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 163 publications
(194 reference statements)
2
23
0
3
Order By: Relevance
“…2 b). We attribute the two peaks with the intra and inter-granular losses for granular superconductors in line with the observations and discussions related to high T c Cuprate superconducting thin films 32 34 . The peak at higher temperatures, T ph (close to T c or the temperature where the diamagnetic shielding response develops in the films) can be associated with the increase in dissipation due to the movement of intra-granular vortices within the superconducting Nb grains.…”
Section: Resultssupporting
confidence: 86%
“…2 b). We attribute the two peaks with the intra and inter-granular losses for granular superconductors in line with the observations and discussions related to high T c Cuprate superconducting thin films 32 34 . The peak at higher temperatures, T ph (close to T c or the temperature where the diamagnetic shielding response develops in the films) can be associated with the increase in dissipation due to the movement of intra-granular vortices within the superconducting Nb grains.…”
Section: Resultssupporting
confidence: 86%
“…To fulfil this criterion, vortices in the material have to be strongly pinned. Many possibilities to inhibit vortex motion have been found that led to an increase of the superconducting critical current density, J c [ 6 ]. Some of the methods developed to introduce natural and artificial pinning centers are: microstructural variations [ 7 , 8 ], creation of oxygen vacancies [ 9 ], the addition of secondary phases [ 10 , 11 ], magnetic nanoparticles, or nanolayers [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…1−4 Superconducting REBa 2 Cu 3 O 7 (REBCO, RE = rare earth) films and coated conductors (CC) possess an inherent advantage due to the high performances in a significantly broad spectrum of the magnetic field−temperature (B−T) diagram, hence showing promising properties for wide market implementation. 5 Due to historical reasons, YBCO has been the most investigated REBCO superconductor. 6 Nevertheless, a wide range of RE ions that can replace Y are driving the current research interest.…”
Section: ■ Introductionmentioning
confidence: 99%